PROVERBIAL PLAY: J.R.R. TOLKIEN’S USE OF PROVERBS IN THE HOBBIT AND THE LORD OF THE RINGS - Clinton, Esther (Proverbium - Yearbook, 2014)
Proverbs are a significant part of the linguistic complexity that Tolkien created for Middle Earth: both Tolkien as narrator/author and many of his characters use them. This article discusses Tolkien’s use of proverbs, including the question of how and why he indicates proverbiality when he creates new proverbs. Tolkien’s use and creation of proverbs reminds readers that Middle Earth has a history that has affected (and been affected by) language and language use.